Comparative chloroplast genome analyses of 23 species in Swertia L. (Gentianaceae) with implications for its phylogeny - Yang, Lucun; Li, Jingjing; Zhou, Guoying (Frontiers in Genetics, 2022)
Swertia L. is a large genus in the family Gentianaceae. Different chloroplast gene segments have been used to study the systematic evolutionary relationships between species of Swertia L. However, as gene fragment-based phylogenies lack sufficient resolution, the systematic evolutionary relationships between Swertia L. species have remained unclear. We sequenced and annotated the complete chloroplast genomes of four Swertia species, namely Swertia bifolia, Swertia tetraptera, Swertia franchetian, and Swertia przewalskii, using next generation sequencing and the plastid genome annotator tool. The chloroplast genome sequences of 19 additional species of Swertia L. were downloaded from NCBI database and also assessed. We found that all 23 Swertia L. species had a similar genetic structure, i.e., a ring tetrad structure, but with some clear differences. The chloroplast genomes of the 23 Swertia L. species were 149,036–153,691 bp long, averaging 152,385 bp; the genomes contained 134 functional genes: 38 tRNA, and eight rRNA, and 88 protein-encoding genes. Comparative analysis showed that chloroplasts genome of Swertia were conserved in terms of genome structure, codon preference and repeat sequences, but differed in terms of genome sizes, gene contents and SC/IR boundary. Using Swertia wolfangiana as a reference, we found clear divergences in most of the noncoding and intergenic regions of the complete chloroplast genomes of these species; we also found that the rpoC1, ccsA, ndhI, ndhA, and rps15 protein-coding genes had large variations. These highly variable hotspots will be useful for future phylogenetic and population genetic studies. Phylogenetic analysis with high bootstrap support showed that Swertia L. was not monophyletic. The classification of subgen. Swertia and subgen. Ophelia was supported by molecular data, which also partly supported the division of sect. Ophelia, sect. Platynema, sect. Poephila, sect. Swertia, and sect. Macranthos. However, the systematic positions of other groups and species require further exploration. The Swertia L formed at 29.60 Ma. Speciation of 10 species occurred in succession after 12 Ma, and 13 species occurred in succession after 2.5 Ma. Our analysis provides insight into the unresolved evolutionary relationships of Swertia L. species.